2012
DOI: 10.1155/2012/593405
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of Indian Mothers with Children Having Severe-to-Profound Hearing Impairment at Diagnosis and after 1–3 Years of Therapy

Abstract: Counseling training in graduate programs continues to be underrepresented. If parental queries are not addressed adequately, they keep visiting one doctor after another. Objective. The aim of the study is to identify maternal needs of children with hearing impairment at two stages of habilitation, that is, just after diagnosis (group I) and after receiving 1 to 3 years of language therapy (group II). Methods. Two groups of mothers were asked to speak their queries about aural habilitation of their children. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Similarly, young children are not able to read or write because limited academic skills. It is very important to make sure that test items are selected from their vocabulary list only to correct interpretation of speech perception ability [19][20][21]39,41,54,58,60,68,77,87,85]. Speech perception ability of young children only can be inferred by child response.…”
Section: Considerations In the Development Of The Testsmentioning
confidence: 99%
“…Similarly, young children are not able to read or write because limited academic skills. It is very important to make sure that test items are selected from their vocabulary list only to correct interpretation of speech perception ability [19][20][21]39,41,54,58,60,68,77,87,85]. Speech perception ability of young children only can be inferred by child response.…”
Section: Considerations In the Development Of The Testsmentioning
confidence: 99%
“…Typically, the confirmation of an auditory impairment is followed by a sequence of social and emotional transformations starting with shock and bewilderment, through a period of doubt and denial, to a final acceptance of the child's status. Poor handling of the diagnostic process in itself may exacerbate the emotional and psychological burden for the family [62]. In some traditional communities where unfavorable and superstitious beliefs towards childhood disabilities prevail, the diagnosis of an auditory impairment may be attributed to sorcery and other supernatural factors regardless of the etiology, causing further emotional torment for the parents [57].…”
Section: Impact Of Hearing Impairment On the Familymentioning
confidence: 99%
“…Families may also be troubled by the ensuing and inevitable social stigma that will follow when the diagnosis of an auditory impairment becomes publicly apparent [55e57,63]. One study from India also found that, at diagnosis, mothers of infants with severeto-profound hearing impairments were concerned about how to cope with the emotional aspect of hearing loss [62].…”
Section: Impact Of Hearing Impairment On the Familymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the analysis of the parents' responses reported that families may experience strong emotions, including denial, sadness, and shock at the time of diagnosis of hearing loss, and therefore may need counselling and adequate emotional support. A need for emotional support to deal with the challenges associated with hearing loss has been reported in international studies too (Alqahtani, 2017;Davids & De Jager, 2018;Rout & Khanna, 2012). However, the majority (85%) of Australian families (n = 445) who completed a written survey in Scarinci et al's (2018) mixed methods study reported that they were satisfied with the emotional and personal support they received, and only one fifth of the families were not satisfied with the emotional support of some professionals and mostly from the diagnostic audiologists and General Practitioners.…”
Section: Needs Of Families Of Children With Hearing Lossmentioning
confidence: 99%